Karakteristik Sensoris Ikan Lele Sangkuriang (Clarias gariepinus) Berbumbu dengan Perbedaan Teknik Budidaya dan Ukuran Ikan - Selly Ratna Sari; Guttifera Guttifera; Raudhatus Sa’adah; Elmeizy Arafah (Universitas Sriwijaya, 2020)
This research aims to determine preference level for catfish (Clarias gariepinus) spiced with differences technique in organic Aquaculture and non-organic Aquaculture as well as differences in fish size. This research treatment used the method of aquaculture and difference in the size of fish. Aquaculture method (A) namely A1= Conventional and A2= Organic while the second treatment was the difference in the weight of fish (B) namely B1= 100 g, B2= 200 g and B3= 300 g. The spiced catfish was cooked by way of deep-fried Further sensory testing. The method used in this research was the method of experimentation and statistical analysis used the Friedman Conover test. The results indicated that fish had the best texture, aroma and taste in the A2B1 treatment.